Late effects, long‐term problems and unmet needs of cancer survivors. Issue 8 (17th June 2022) - Schmidt, Martina E.; Goldschmidt, Siri; Hermann, Silke; Steindorf, Karen
Abstract: Great efforts are being made in cancer treatment, with impressive improvement in survival. The situation concerning research and care for long‐term problems and late effects in the growing population of cancer survivors, however, is unsatisfactory. Therefore, in the FiX survey 1348 disease‐free survivors about 4 years after diagnosis of different cancer types were asked to rate existing burdens and support received for them along a list of 36 potential problems. Health‐related quality of life (HRQoL) was assessed with the EORTC QLQ‐C30. Determinants of burdens were explored using logistic regression analysis. While cancer survivors' global HRQoL, physical and role function ratings were comparable or better than age‐ and sex‐matched reference values of the general population, emotional and cognitive function was worse, especially among women ( P  < .01). Most frequently reported problems with at least moderate burden were loss of physical performance (36.3%), fatigue (35.1%), sexual problems (34.7%), sleep problems (34.1%), arthralgia (33.8%), anxiety (28.0%), neuropathy (25.6%), memory problems (23.0%) and concentration problems (21.9%). Burdened survivors often rated received support as poor, especially regarding support for problems that physicians might consider medically nonthreatening, or for which no effective pharmacologic or medical treatment is known. Determinants for burden included higher age, female gender, having ever received chemotherapy and overweight/obesity. In conclusion, a significant number of cancer survivors suffer from long‐term or late effects and have unmet care needs. Awareness of health care professionals should be increased for these issues. The results of our study can contribute to the development of targeted survivorship plans. What's new?: Long‐term effects of cancer and its treatment as well as psycho‐social issues may hinder a return to normal life in cancer survivors. Evidence on which long‐term problems are the most burdensome for cancer survivors remains scarce, however. Here, more than one‐third of disease‐free cancer survivors reported specific physical, psychological, cognitive, social, and sexual problems 4 years after diagnosis. Significant determinants including prior chemotherapy, obesity, and cancer type were identified, and cancer survivors often rated care satisfaction as poor. The study may raise healthcare professionals' awareness of long‐term problems in cancer patients and support the development of evidence‐based, tailored survivorship plans.